Synergising Hallyu and halal economy for wealth creation - Adlin Masood,; Alina Abdul Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
South Korea has reaped economic success from international acceptance of Hallyu and now eyes Halal economy as an added avenue of sustainable economic well-being. Merging Hallyu concepts with Korean made Halal products are alternative avenues for income generation. However, their industry players face considerable difficulties as they have poor knowledge about Islam, plus only one South Korea Halal certification body is acknowledged globally, thus to obtain Halal certification is problematic. It’s imperative that stakeholders implement the Halal standards in order to export their cosmetics and food products to the Asian and Middle East markets, and realise Muslim friendly tourism within their country. Malaysia, a multiracial nation is universally acclaimed as a leader in Islamic Economy. By using Malaysia’s experience, South Korea’s policy makers and business sectors will be able to identify the gaps in Islamic knowledge between the expected and that practised. Business success in the Halal market is the motivating driver to understand Islam and made possible via experiential learning. A literature review will be conducted by analysing existing documents on Halal economy; Korea’s economy, culture and awareness of Halal. Findings will assist in charting what areas should be addressed to create greater understanding about halal and Islam.